IMPLEMENTASI KEBIJAKAN PENGEMBANGAN MANAJEMEN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) KOTA SALATIGA - Eirene Laura Juwita Herawati; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
This study aims to deeply analyze the implementation of the Electronic-Based Government System (SPBE) policy in Salatiga City and to identify the supporting and inhibiting factors in its execution. SPBE is a strategic initiative by the Indonesian government to achieve clean, effective, transparent, and accountable governance through the integrated use of information and communication technology (ICT). Using a descriptive qualitative approach with a case study method, this research explores the implementation complexities behind quantitative achievements. Data were collected through in-depth interviews with key local government officials, non-participant observation, and document analysis of SPBE-related policies. The findings reveal a paradox: although Salatiga City achieved a "Very Good" rating in the national SPBE Index, the SPBE Management Domain itself shows low performance. Implementation has proceeded gradually, marked by the establishment of institutional structures, the development of digital services, and the integration of information systems. However, the policy's execution still faces serious obstacles, including limited and uneven technological infrastructure, a scarcity of competent human resources in ICT, low digital literacy among officials and the public, and challenges in inter-agency coordination exacerbated by sectoral egos. On the other hand, leadership commitment, clear regulations, and the successful adoption of several national applications are supporting factors. This study concludes that the high SPBE achievement is more superficial and driven by meeting service indicators, while its managerial foundation remains fragile. Strategic strengthening of human resource capacity, increased infrastructure budget allocation, bureaucratic management reform, and active public participation are essential to achieving the goals of SPBE optimally and sustainably.